2014
DOI: 10.4238/2014.february.27.2
|View full text |Cite
|
Sign up to set email alerts
|

Risk analysis of duo parentage testing with limited STR loci

Abstract: ABSTRACT. The aim of this study was to evaluate whether the Goldeneye 20A system (containing 19 short tandem repeats) can avert the shortage of duo parentage tests. Among routine cases typed by the Identifiler system, we identified 42 motherless cases, 2 fatherless cases, and 34 trio cases containing 1 locus mismatch and 4 motherless cases with 2 locus mismatches. One true trio case was rejected by fatherhood testing because of the omission of the mother's genotype and because the genotype of the putative fath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…In general, the false inclusion rate ranges between 19% and 23% [40]. These problems are being reported more frequently and are most common in cases where only one putative parent is available [31,40,42]. The inclusion of additional autosomal STR loci may assist in clarifying some ambiguous cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the false inclusion rate ranges between 19% and 23% [40]. These problems are being reported more frequently and are most common in cases where only one putative parent is available [31,40,42]. The inclusion of additional autosomal STR loci may assist in clarifying some ambiguous cases.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, however, the addition of more loci introduces additional mismatches. Furthermore, it has been observed that the inclusion of more loci does not compensate for the absence of genetic information from the mother or the father [35,40,[42][43][44]. The use of Y-chromosome STRs can help only when the victim is male, and the possibility that a close relative of the putative father is the biological father cannot be ruled out [45].…”
Section: Discussionmentioning
confidence: 99%